Architecting Hybrid Contract in al-Rahn: A Comparative Study between Malaysia and Indonesia - Muhammadi, Fauzan; Mohd Razif, Nor Fahimah; Rahim, Rahimin Affandi Abdul (Indonesian Comparative Law Review, 2023)
Nowadays, hybrid contracts are recognized as an adaptive form of contract in the implementation of Islamic business. However, the involvement of hybrid contracts in al-Rahn has risen numerous legal controversies in Islamic Sharia.  Malaysia and Indonesia  have diffferent approaches regarding the  use of hybrid contracts in al-Rahn scheme. In the light of that, this article aims to lay out the two countries’ sides in responding to the issue at hand. This qualitative  study  relies on secondary data and employs conceptual and comparative approach. It investigates the policies relating to hybrid contract in the implementation of al-Rahn both in Malaysia and Indonesia. This study indicates that academics in both countries tend to state that the hybrid contracts in al-Rahn are not in accordance with the Sharia. The non-compliance with the Sharia prompted Malaysia to create a new policy, namely by utilising the concept of Tawaruq. Meanwhile, Indonesia recently still associates Ijārah contracts as part of the implementation of al-Rahn.